Movimento negro de São Carlos e a UFSCar : a extensão universitária sobre relações étnico-raciais - Souza, Danielle Felisberto de (2017)
The present work had as its objective discussing the relationship between the Black Movement and the university, through the axis of university extension, analyzing the extension activities that deal with the subject of racial and ethnic relations and from the perspective of representatives of groups of the black movement of São Carlos and UFSCar members. In this work, we attempted to answer the question: what are the advances and limits of the UFSCar extension activities for the groups of the Black Movement of São Carlos, involving the theme of racial and ethnic relations? We used qualitative methodology, divided in the stages of bibliographical survey, interviews, analysis and interpretation of the data. This work allowed us to reflect, discuss and study the advances and limits of the role of the university in the relation with the community, through extension. It is perceived that this relationship is permeated by many contributing elements moving the dialogue forward or backward and that it is necessary to understand the university from the totality in which it is inserted. The university has a fundamental role in making a historical, sociological and political survey of the situation of black people, formulating actions, giving new meanings to historical stigmas, and strengthening the relationship with the external community through teaching, research and extension. However, this relationship is limited by the political sphere, since it is through this sphere that it will be possible to implement public policies. Thus, the university must be attentive to those actions that can contribute to the separation and non-belonging of the external community. Extension can serve as a mechanism to reinforce social inequality, and the actions that contribute to the transformation end up being restricted only those teachers who already had a social commitment. Therefore, it is necessary to have a constant reflection on this relation so that the university assumes its social commitment.